2018
DOI: 10.3390/molecules23030622
|View full text |Cite
|
Sign up to set email alerts
|

Which Dendrimer to Attain the Desired Properties? Focus on Phosphorhydrazone Dendrimers

Abstract: Among the six Critical Nanoscale Design Parameters (CNDPs) proposed by Prof. Donald A. Tomalia, this review illustrates the influence of the sixth one, which concerns the elemental composition, on the properties of dendrimers. After a large introduction that summarizes different types of dendrimers that have been compared with PolyAMidoAMine (PAMAM) dendrimers, this review will focus on the properties of positively and negatively charged phosphorhydrazone (PPH) dendrimers, especially in the field of biology, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…One of the inorganic branching points of dendrimers is the phosphorous-generating the family of “Phosphorhydrazone dendrimers”. Terminal functions can have positive charges (ammonium) or negative charges (phosphonates) [ 33 ]. These structures are presented in Figure 9 .…”
Section: Biomedical Applications Of Dendrimersmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the inorganic branching points of dendrimers is the phosphorous-generating the family of “Phosphorhydrazone dendrimers”. Terminal functions can have positive charges (ammonium) or negative charges (phosphonates) [ 33 ]. These structures are presented in Figure 9 .…”
Section: Biomedical Applications Of Dendrimersmentioning
confidence: 99%
“… The structures of phosphorhydrazone dendrimers with charged terminal functions: positive ( a ) and negative ( b ). Adapted from [ 33 ], published by Molecules 2018. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, interaction through electrostatic surface charges is not the only mechanism whereby NPs lead to platelet aggregation, and each nanosystem must be investigated as an independent case [60]. Amongst the different nanosystems, dendrimers stand out in terms of their ability to induce platelet aggregation; numerous types of dendrimers, including polyamiodamine (PAMAM), polypropyleneimine (PPI), triazine and carbosilane dendrimers, have been found to cause aggressive thrombus formation [61]. PAMAM dendrimers specifically have been extensively studied for their hemotoxicity and effects on blood platelets, especially after Greish et al found amine-terminated PAMAM dendrimers to cause a lethal, disseminated intravascular coagulation-like condition in CD1 mice [62].…”
Section: Platelet Function In Hemostasis and The Mechanisms Involvmentioning
confidence: 99%
“…[92]. Carbon nanotubes are graphite sheets rolled up into a tubular form in which drugs are filled [93].…”
Section: Nanoparticles As Vehicles For Gene Deliverymentioning
confidence: 99%